Crosslinkable acrylic rubber composition
By using a crosslinkable composition composed of copolymeric anti-aging agents and phenothiazine anti-aging agents in acrylic rubber, softening and curing deterioration during thermal oxidation are suppressed, and the reduction of mechanical strength in the prior art is solved. The problem of heat resistance in high temperature environments has been improved.
Patent Information
- Application Number
- CN202380039480.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-19
- Filing Date
- 2023-03-10
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art cannot effectively suppress the significant softening and curing deterioration of acrylic rubber during thermal oxidation, and the mechanical strength is reduced, making it unable to meet the heat resistance needs in high temperature environments.
The crosslinked acrylic rubber composition consisting of the general formula [I] copolymerizable anti-aging agent, phenothiazine anti-aging agent, polyamine crosslinking agent and crosslinking accelerator is adopted, and the copolymerizable anti-aging agent is used in a high-end manner. The molecular side chains contain anti-aging components and inhibit thermal oxidation deterioration through chemical bonding.
It significantly inhibits the reduction of mechanical strength of acrylic rubber crosslinks, extends the life of rubber molded components, and maintains mechanical properties in harsh environments.
Smart Images

Figure CN119173578A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a cross-linkable acrylic rubber composition, and more particularly to a cross-linkable acrylic rubber composition capable of minimizing the reduction in mechanical properties of a cross-linked product due to thermal oxidative degradation. Background Art
[0002] From the perspective of global climate change countermeasures and efficient use of energy, there are carbon dioxide and NO emissions from internal combustion engines such as automobile engines. x The emission control of gases and the like is becoming increasingly strict. As a countermeasure, automobile engines are required to have high output, high thermal efficiency, and reduced and harmless exhaust gases, so there is a tendency for the temperature in the engine room to rise. In conjunction with this, the polymer materials such as rubber and plastics used in the surrounding areas are required to have further improved heat resistance.
[0003] As a specific example, vehicles equipped with turbocharger systems are becoming more common in order to improve the fuel efficiency of the engine. Since the air introduced from the turbocharger to the intercooler or the engine is high temperature and high pressure, the rubber hose material for conveying the air is required to have high heat resistance.
[0004] Thus, as the use environment of polymer materials used in automobile engines becomes hotter and their lifespan becomes longer, measures such as improving the heat resistance of the raw rubber of rubber product parts or adding appropriate anti-aging agents to rubber product parts can be taken as countermeasures.
[0005] As a typical antioxidant for rubber members, a phenolic antioxidant or an amine antioxidant can be used. In particular, for rubber members used in a higher temperature usage environment, an amine antioxidant can be used.
[0006] For example, in the case of acrylic rubber, as an antioxidant, an amine antioxidant represented by 4,4′-bis(α,α-dimethylbenzyl)diphenylamine can be used (Patent Documents 1 to 4).
[0007] In addition, as a measure to improve the heat resistance of acrylic rubber itself, by changing the crosslinking site monomer from an unsaturated monomer containing active chlorine to an α,β-unsaturated carboxylic acid monomer, a strong crosslinking structure that can withstand use in a high temperature environment can be formed.
[0008] However, even if the heat resistance of the raw rubber itself is improved and an amine antioxidant is used, it is still not possible to fully meet the recent heat resistance requirements.
[0009] Patent Document 5 describes that phenothiazine-based antioxidants are effective as antioxidants for rubber materials.
[0010] This document discloses a rubber material which is excellent in vulcanization properties, mechanical properties and heat aging properties and is particularly suitable for anti-vibration rubber applications. The rubber material contains (A) a diene rubber, (B) a bismaleimide compound and (C) the following phenothiazine compound.
[0011]
[0012] R 1 , R 2 : hydrogen atom, C1-C8 alkyl group which may be substituted by an aromatic ring, alkoxy group, halogen atom, cyano group;
[0013] R 3 : Hydrogen atom, C1-C6 chain or cyclic alkyl, vinyl, aromatic group;
[0014] m, n: 0~2.
[0015] Phenothiazine compounds in which the sulfur atom at the 5-position is -SO2- are also known, and are described in Patent Document 6, for example.
[0016] Patent document 6 describes a fused heterocyclic compound represented by the following general formula and an organic material composition containing the fused heterocyclic compound. It is described that the organic material composition can impart higher processing stability, heat resistance, and long life to organic materials such as polymers that are susceptible to oxidation, heat, or photo-induced breakdown.
[0017]
[0018] Y: chemical single bond, -S(=O)-, -SO2-;
[0019] R a , R b :C1~C 30 Organic groups;
[0020] Z a , Z b : Chemical single bond, -SO2-;
[0021] X 1 , X 2 :Hydrogen atom, halogen atom, alkyl group, cyano group, nitro group, -OR 1 、-O-CO-R 1 、-CO-OR 1 、-O-CO-OR 1 、-NR 2 R 3 、-NR 2 -CO-R1 、-CO-NR 2 R 3 、-O-CO-NR 2 R 3 ;
[0022] n, m: 0 to 2, either of which is not 0.
[0023] In addition, in order to prevent the amine antioxidant from volatilizing from the rubber component, research is being conducted on the high molecular weight and high melting point of the amine antioxidant. However, with the high molecular weight and high melting point of the antioxidant, there are problems such as reduced dispersibility in rubber and reduced mobility in the rubber.
[0024] In order to prevent the volatilization of the antioxidant and extend the life of rubber parts in high temperature environments, a method of copolymerizing an antioxidant having a polymerizable unsaturated group with a raw rubber is also being studied (Patent Document 7).
[0025] For example, Non-Patent Documents 1 and 2 exemplify anti-aging agents having a polymerizable unsaturated group, such as Nocrac G-1 (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) and APMA (manufactured by Seiko Chemical Industry Co., Ltd.).
[0026]
[0027] However, among the above-mentioned antioxidants, it is practically difficult to perform radical copolymerization with a polymerizable unsaturated monomer due to the radical polymerization inhibitory effect of the diphenylamino group.
[0028] In addition, several methods for introducing a diphenylamino structure into a polymer by a modification reaction of an elastomeric polymer have been disclosed. For example, there are known methods for introducing a diphenylamino group by hydroformylating the side chain of an elastomer having an ethylenically unsaturated group (Patent Document 8); and a method for introducing a diphenylamino group by adding maleic anhydride to a diene copolymer in the presence of a free radical generator (Patent Document 9). However, these methods also require a modification step of introducing a diphenylamino group after manufacturing a base copolymer, which is not practical in terms of manufacturing cost.
[0029] Furthermore, a method of crosslinking acrylic rubber in the co-presence of 4-aminodiphenylamine is known (Patent Documents 10 and 11). However, in this method, 4-aminodiphenylamine may deteriorate the compression set resistance.
[0030] Thus, in the prior art, no matter which method is used to improve the heat resistance of the raw rubber itself, improve the performance of various anti-aging agents, or chemically bond the heat-resistant aging component to the raw rubber, the recent heat resistance requirements cannot be fully met.
[0031] Prior art literature
[0032] Patent Literature
[0033] Patent Document 1: Japanese Patent Application Laid-Open No. 11-21411
[0034] Patent Document 2: WO 2011 / 58918A1
[0035] Patent Document 3: Japanese Patent Application Publication No. 2010-254579
[0036] Patent Document 4: WO 2006 / 001299 A1
[0037] Patent Document 5: Japanese Patent Application Publication No. 2015-227402
[0038] Patent Document 6: WO 2011 / 093443 A1
[0039] Patent Document 7: Japanese Patent Application Publication No. 2009-209268
[0040] Patent Document 8: Japanese Patent Application Laid-Open No. 4-264106
[0041] Patent Document 9: Japanese Patent Application Laid-Open No. 5-230132
[0042] Patent Document 10: WO 2020 / 158132 A1
[0043] Patent Document 11: Japanese Patent Application Publication No. 2009-84514
[0044] Patent Document 12: Japanese Patent Application Publication No. 2020-111552
[0045] Non-patent literature
[0046] Non-patent document 1: Rubber Chem. Technol., Vol. 46, p. 106 (1973)
[0047] Non-patent document 2: Rubber Chem. Technol., Vol. 52, p. 883 (1979)
[0048] In view of the above problems, the inventors of the present invention have studied whether the heat resistance of acrylic rubber can be improved by a cross-linkable acrylic rubber composition composed of an acrylic rubber containing an anti-aging component and a carboxyl group, a phenothiazine-based anti-aging agent, a cross-linking agent, and a cross-linking accelerator. In particular, the inventors have studied for the purpose of suppressing the significant softening degradation observed in the early stage of thermal oxidative degradation of acrylic rubber containing ethyl acrylate as a main raw material and the significant curing degradation observed in the later stage. Summary of the invention
[0049] Problems to be solved by the invention
[0050] The present invention has been made in view of the above problems, and an object of the present invention is to provide a cross-linkable acrylic rubber composition which suppresses the significant softening degradation observed in the early stage of thermal oxidative degradation of acrylic rubber cross-linked products and the significant curing degradation observed in the later stage thereof, and minimizes the reduction in mechanical strength thereof.
[0051] Technical means to solve problems
[0052] The above-mentioned object of the present invention can be achieved by the cross-linkable acrylic rubber composition as described below, wherein the cross-linkable acrylic rubber composition contains the following components:
[0053] (A) an acrylic elastomer copolymer composed of a copolymerizable antioxidant represented by the general formula [I], an alkyl (meth)acrylate monomer and / or an alkoxyalkyl (meth)acrylate monomer and an α,β-unsaturated carboxylic acid monomer;
[0054]
[0055] (In general formula [I], R 1 is a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, R 2 is a hydrogen atom or a methyl group, and A is a direct bond, an oxygen atom or a sulfur atom)
[0056] (B) a phenothiazine antioxidant represented by the general formula [II];
[0057]
[0058] [In the general formula [II], R 3 is a hydrogen atom, a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, or an acyl group represented by the following general formula [III], R 4 is an aralkyl group having 7 to 20 carbon atoms]
[0059]
[0060] (In the general formula [III], R 5 is a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms)
[0061] (C) a polyamine cross-linking agent; and
[0062] (D) Cross-linking accelerator.
[0063] Effects of the Invention
[0064] The acrylic elastomer copolymer used in the cross-linkable acrylic rubber composition of the present invention contains an anti-aging component in the polymer side chain, and the copolymer itself is stable against thermal oxidative degradation. In addition, in a molded part obtained by cross-linking the acrylic elastomer copolymer, the anti-aging component can be prevented from volatilizing into the air or being extracted by a liquid medium such as oil or an organic solvent, resulting in a feature of being able to extend the life of the acrylic elastomer molded part in various adverse environments.
[0065] In addition, due to the crosslinking effect of the anti-aging component chemically bonded to the polymer side chain, softening degradation observed in the early stage of thermal oxidative degradation can be suppressed, and a decrease in mechanical strength can be suppressed.
[0066] Furthermore, in the late stage of thermal oxidative degradation of the acrylic rubber cross-linked product copolymerized with the copolymerizable antioxidant, the phenothiazine antioxidant constituting the composition of the present invention exerts a remarkable effect of inhibiting curing degradation. As a result, the following excellent effect can be exerted: the molded component obtained by cross-linking the cross-linkable acrylic rubber composition of the present invention can minimize the reduction in its mechanical properties during the entire thermal oxidative degradation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 It is a graph showing the change over time of the 100% modulus of the acrylic rubber cross-linked product at 190° C. (Example 1: -●-, Comparative Example 1: --●--, Comparative Example 2: --▲--, Comparative Example 3: --◆--; Figure 1 to Figure 3 General).
[0068] Figure 2 This is a schematic diagram showing the change over time in the breaking strength of an acrylic rubber cross-linked product at 190°C.
[0069] Figure 3 This is a schematic diagram showing the change over time in the elongation at break of an acrylic rubber cross-linked product at 190°C.
[0070] Figure 4 It is a graph comparing the change rate of breaking strength (black column) after a composite test (including air heating (175°C, 150 hours), IRM903 oil immersion (150°C, 168 hours) and air heating (190°C, 300 hours)) with the change rate of breaking strength (white column) after an air heating aging test (190°C, 300 hours).
[0071] Figure 5It is a graph comparing the change in elongation at break (black column) after a composite test (including air heating (175°C, 150 hours), IRM903 oil immersion (150°C, 168 hours) and air heating (190°C, 300 hours)) with the change in elongation at break (white column) after an air heating aging test (190°C, 300 hours).
[0072] Figure 6 It is a graph showing the change with time of the 100% modulus of the acrylic rubber cross-linked product at 190° C. (Example 2: -●-, Comparative Example 4: --●--, Comparative Example 5: --▲--, Comparative Example 6: --◆--; Figure 6 to Figure 8 General).
[0073] Figure 7 This is a schematic diagram showing the change over time in the breaking strength of an acrylic rubber cross-linked product at 190°C.
[0074] Figure 8 This is a schematic diagram showing the change over time in the elongation at break of an acrylic rubber cross-linked product at 190°C.
[0075] Fig. 9 It is a graph showing the change over time of the 100% modulus of the acrylic rubber cross-linked product at 190° C. (Example 3: -●-, Comparative Example 7: --●--, Comparative Example 8: --▲--, Comparative Example 9: --◆--; Figures 9 to 11 General).
[0076] Fig.10 This is a schematic diagram showing the change over time in the breaking strength of an acrylic rubber cross-linked product at 190°C.
[0077] Fig.11 This is a schematic diagram showing the change over time in the elongation at break of an acrylic rubber cross-linked product at 190°C.
[0078] Fig.12 It is a graph showing the change with time of the 100% modulus of the acrylic rubber cross-linked product at 190° C. (Example 4: -●-, Comparative Example 10: --●--, Comparative Example 11: --▲--, Comparative Example 12: --◆--; Figure 12 to Figure 14 General).
[0079] Fig.13 This is a schematic diagram showing the change over time in the breaking strength of an acrylic rubber cross-linked product at 190°C.
[0080] Fig.14 This is a schematic diagram showing the change over time in the elongation at break of an acrylic rubber cross-linked product at 190°C.
[0081] Fig.15 It is a graph comparing the change in elongation at break (black column) after a composite test (including toluene immersion (room temperature, 168 hours) and air heating (190°C, 300 hours)) with the change in elongation at break (white column) after an air heating aging test (190°C, 300 hours). DETAILED DESCRIPTION
[0082] The cross-linkable acrylic rubber composition of the present invention contains the following components:
[0083] (A) an acrylic elastomer copolymer composed of a copolymerizable antioxidant represented by the general formula [I], an alkyl (meth)acrylate monomer and / or an alkoxyalkyl (meth)acrylate monomer and an α,β-unsaturated carboxylic acid monomer;
[0084]
[0085] (In general formula [I], R 1 is a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, R 2 is a hydrogen atom or a methyl group, and A is a direct bond, an oxygen atom or a sulfur atom)
[0086] (B) a phenothiazine antioxidant represented by the general formula [II];
[0087]
[0088] [In the general formula [II], R 3 is a hydrogen atom, a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, or an acyl group represented by the following general formula [III], R 4 is an aralkyl group having 7 to 20 carbon atoms]
[0089]
[0090] (In the general formula [III], R 5 is a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms)
[0091] (C) a polyamine cross-linking agent; and
[0092] (D) a cross-linking accelerator;
[0093] Here, (meth)acrylate refers to acrylate or methacrylate.
[0094] The copolymerizable antioxidant represented by the general formula [I] used in the acrylic elastomer copolymer (A) can be easily produced from phenothiazine, phenoxazine, carbazole, etc. An example of the production method is shown below.
[0095]
[0096] After N-alkylation is performed in the first step, the aromatic ring is formylated or acetylated, and then the carbonyl group is converted into an olefin, thereby being able to produce the target copolymerizable antioxidant.
[0097] Specific examples of copolymerizable antioxidants include:
[0098]
[0099] wait.
[0100] When the copolymerizable anti-aging agent is copolymerized with the polymerizable unsaturated monomer, the copolymerizable anti-aging agent [I] is used in a ratio of about 0.05 to 5 parts by weight, preferably about 0.1 to 3 parts by weight, relative to 100 parts by weight of the (meth) alkyl acrylate and / or (meth) alkoxyalkyl acrylate monomer. If it is used in a ratio below the above range, sufficient anti-aging effect cannot be expected. On the other hand, if it is used in a ratio above the above range, improvement in anti-aging effect cannot be expected and it is not economical.
[0101] As the (meth)acrylate alkyl ester monomer and / or (meth)acrylate alkoxyalkyl ester monomer constituting the acrylic elastomer copolymer of the present invention, at least one (meth)acrylate selected from the group consisting of (meth)acrylate alkyl esters having an alkyl group having 1 to 8 carbon atoms, (meth)acrylate aralkyl esters having an aralkyl group having 7 to 20 carbon atoms, and (meth)acrylate alkoxyalkyl esters having an alkoxyalkyl group having 2 to 8 carbon atoms can be used.
[0102] As the alkyl (meth)acrylate, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. can be used. Two or more of them can also be used in combination. It is preferred to use two alkyl (meth)acrylates of ethyl acrylate, ethyl acrylate and butyl acrylate.
[0103] As the aralkyl (meth)acrylate, for example, benzyl (meth)acrylate or the like can be used.
[0104] Examples of the alkoxyalkyl (meth)acrylate include methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, n-butoxyethyl (meth)acrylate, ethoxypropyl (meth)acrylate, methoxyethoxyethyl (meth)acrylate, and ethoxyethoxyethyl (meth)acrylate.
[0105] Examples of the α,β-unsaturated carboxylic acid monomer constituting the acrylic elastomer copolymer as the component (A) include α,β-unsaturated monocarboxylic acids, α,β-unsaturated dicarboxylic acids, and α,β-unsaturated dicarboxylic acid monoalkyl esters.
[0106] Examples of the α,β-unsaturated monocarboxylic acid include acrylic acid and methacrylic acid.
[0107] Examples of the α,β-unsaturated dicarboxylic acid include maleic acid, fumaric acid, itaconic acid, and citraconic acid.
[0108] Examples of the α,β-unsaturated dicarboxylic acid monoalkyl esters include monoalkyl esters of maleic acid, fumaric acid, itaconic acid, and citraconic acid. Specific examples include monomethyl maleate, monoethyl maleate, mono-n-propyl maleate, monoisopropyl maleate, mono-n-butyl maleate, monoisobutyl maleate, mono-n-hexyl maleate, monocyclohexyl maleate, monomethyl fumarate, monoethyl fumarate, mono-n-propyl fumarate, monoisopropyl fumarate, mono-n-butyl fumarate, monoisobutyl fumarate, mono-n-hexyl fumarate, and monocyclohexyl fumarate.
[0109] The crosslinking site monomer in the acrylic elastomer copolymer (A) is copolymerized in a ratio of 0.1 to 5% by weight, preferably 0.5 to 3% by weight.
[0110] Furthermore, in addition to the main component of the acrylic elastomer copolymer (A) component, other polymerizable unsaturated monomers may be used as necessary.
[0111] Examples of the polymerizable unsaturated monomer include styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 1-vinylnaphthalene, 2-vinylnaphthalene, acrylonitrile, methacrylonitrile, acrylamide, vinyl acetate, methyl vinyl ether, ethyl vinyl ether, ethylene, propylene, piperylene, butadiene, isoprene, chloroprene, cyclopentadiene, vinyl chloride, and 1,1-dichloroethylene.
[0112] The acrylic elastomer copolymer of component (A) can be produced by a common acrylic rubber copolymerization method. The copolymerization reaction can be carried out by any method such as emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, etc., preferably, emulsion polymerization or suspension polymerization is used, and the reaction is carried out at a temperature of about -10°C to 100°C, preferably about 5°C to 80°C.
[0113] As the polymerization initiator of the reaction, it can be used alone or as a redox system: organic peroxides or hydroperoxides such as benzoyl peroxide, diisopropylbenzene peroxide, tert-butyl hydroperoxide, hydroperoxypropylbenzene, and p-methylene hydroperoxide; diazo compounds such as azobisisobutyronitrile and azobisisobutylamidine; peroxide salts such as ammonium salts, sodium salts, and potassium salts represented by ammonium persulfate, etc.
[0114] As an emulsifier particularly preferably used in the emulsion polymerization method, an anionic or nonionic surfactant can be used in the form of an aqueous solution or the like, which is prepared as a buffer solution using an inorganic salt after pH adjustment with an acid or a base as necessary.
[0115] The polymerization reaction is continued until the conversion rate of the monomer mixture reaches 90% or more. The obtained aqueous latex is coagulated by the following methods: hydrochloric acid coagulation method, method using salts such as calcium chloride, magnesium sulfate, sodium sulfate, ammonium sulfate, method using boron compounds such as boric acid and borax, coagulation method using heat, freezing coagulation method, etc. The obtained copolymer is then thoroughly washed with water and dried. The acrylic rubber has a Mooney viscosity PML of about 5 to 100, preferably about 20 to 80. 1+4 (100℃).
[0116] The acrylic elastomer copolymer of component (A) is an acrylic elastomer copolymer obtained by copolymerizing 0.1 wt% to 5 wt% of a copolymerizable antioxidant represented by the general formula [I], 90 wt% to 99.8 wt% of (meth)acrylic acid alkyl ester and / or (meth)acrylic acid alkoxyalkyl ester monomers, and 0.1 wt% to 5 wt% of an α,β-unsaturated carboxylic acid monomer, preferably 0.3 wt% to 3 wt% of a copolymerizable antioxidant represented by the general formula [I], 94 wt% to 99.2 wt% of (meth)acrylic acid alkyl ester and / or (meth)acrylic acid alkoxyalkyl ester monomers, and 0.5 wt% to 3 wt% of a crosslinking site monomer. Preferably, an acrylic elastomer copolymer composed of a copolymerizable antioxidant represented by the general formula [I], an alkyl acrylate monomer, and an α,β-unsaturated carboxylic acid monomer is used.
[0117] As the component (B) constituting the composition of the present invention, a phenothiazine antioxidant represented by the general formula [II] can be used.
[0118]
[0119] In the general formula [II], R 3 is a hydrogen atom, a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, or an acyl group represented by the following general formula [III], R 4 is an aralkyl group having 7 to 20 carbon atoms,
[0120]
[0121] In the general formula [III], R 5 It is a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms.
[0122] As R 3 Specific examples of the aliphatic hydrocarbon group having 1 to 20 carbon atoms include methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-undecyl, n-pentadecyl, n-heptadecyl, isopropyl, 2-butyl, 2-pentyl, 3-pentyl, 2-hexyl, 3-hexyl, 2-heptyl, 3-heptyl, 4-heptyl, 2-octyl, 3-octyl, 4-octyl, tert-butyl , 1,1-dimethyl-1-propyl, 1,1-dimethyl-1-butyl, 1,1-dimethyl-1-pentyl, 1,1-dimethyl-1-hexyl, 3-methyl-3-pentyl, 3-ethyl-3-pentyl, 3-methyl-3-hexyl, 2-ethylhexyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, 1-methyl-1-cyclopentyl, 1-methyl-1-cyclohexyl, 1-adamantyl, etc.
[0123] As R 3 Specific examples of the aralkyl group having 7 to 20 carbon atoms include benzyl, α-methylbenzyl, and 9-fluorenylmethyl.
[0124] R 5 It is a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms.
[0125] Examples of the aliphatic hydrocarbon group having 1 to 20 carbon atoms include methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-undecyl, n-pentadecyl, n-heptadecyl, isopropyl, 2-butyl, 2-pentyl, 3-pentyl, 2-hexyl, 3-hexyl, 2-heptyl, 3-heptyl, 4-heptyl, 2-octyl, 3-octyl, 4-octyl, tert-butyl, 1 ... ,1-dimethyl-1-propyl, 1,1-dimethyl-1-butyl, 1,1-dimethyl-1-pentyl, 1,1-dimethyl-1-hexyl, 3-methyl-3-pentyl, 3-ethyl-3-pentyl, 3-methyl-3-hexyl, 2-ethylhexyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, 1-methyl-1-cyclopentyl, 1-methyl-1-cyclohexyl, 1-adamantyl, etc.
[0126] Particularly preferred are monovalent aliphatic hydrocarbon groups having 4 to 20 carbon atoms in which the carbon at the α-position relative to the carbonyl group is a tertiary carbon, and examples thereof include tert-butyl, 1,1-dimethylpropyl, 1,1-dimethyl-1-butyl, 1,1-dimethyl-1-pentyl, 1,1-dimethyl-1-hexyl, 3-methyl-3-pentyl, 3-ethyl-3-pentyl, 3-methyl-3-hexyl, 2-ethylhexyl, 1-methyl-1-cyclopentyl, 1-methyl-1-cyclohexyl, and 1-adamantyl.
[0127] As R 4 Examples of the aralkyl group include benzyl, α-methylbenzyl and α,α-dimethylbenzyl, and α,α-dimethylbenzyl is particularly preferred.
[0128] R 3 Phenothiazine antioxidants with hydrogen atoms can be produced by the method described in Patent Document 6. For example, α-methylstyrene is allowed to act on phenothiazine in the presence of an acidic catalyst to produce 3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine (hereinafter referred to as CD-S), and then the sulfur atom is oxidized by an oxidizing agent to produce 3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide (hereinafter referred to as CD-SO2).
[0129] In R 3 In the case of a phenothiazine antioxidant having an aliphatic hydrocarbon group having 1 to 20 carbon atoms, a desired phenothiazine antioxidant can be produced by allowing a base to act on CD-S, followed by N-alkylation with a halide of an aliphatic hydrocarbon having 1 to 20 carbon atoms, and then oxidizing the sulfur atom. Alternatively, a base may be allowed to act on CD-SO2 obtained in Patent Document 6, followed by reacting a halide of an aliphatic hydrocarbon having 1 to 20 carbon atoms.
[0130] In R 3 In the case of an acyl group represented by the general formula [III], it can be produced by the method described in Patent Document 12. Specifically, CD-S is N-acylated with an acyl halide in the presence of a basic organic compound or a basic inorganic compound, and then the sulfur atom is oxidized to produce the desired phenothiazine antioxidant.
[0131] Alternatively, it can be produced by N-acylation of CD-SO2 in the same manner.
[0132] Specific examples of the phenothiazine antioxidant represented by the general formula [III] include: 3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide, 10-methyl-3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide, 10-n-propyl-3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide, 10-isopropyl-3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide. compounds, 10-benzyl-3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide, 10-pivaloyl-3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide, 10-(2,2-dimethylbutyryl)-3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide, 10-(1-adamantanecarbonyl)-3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide, etc.
[0133] The phenothiazine antioxidant of component (B) is used in an amount of about 0.01 to 5 parts by weight, preferably about 0.1 to 5 parts by weight, relative to 100 parts by weight of the acrylic elastomer copolymer of component (A). If the amount of the antioxidant is less than the above range, the mechanical properties of the cross-linked acrylic rubber will be significantly reduced due to thermal oxidation degradation. In particular, it is difficult to suppress the significant curing degradation in the later stage of thermal oxidation degradation. On the other hand, if the amount of the antioxidant is more than the above range, it is not only likely to promote softening degradation in the early stage of thermal oxidation degradation, but also it is impossible to expect the effect of further suppressing curing degradation in the later stage of thermal oxidation degradation, which is not economical.
[0134] As the polyamine crosslinking agent of the component (C), aliphatic polyamine compounds, carbonates of aliphatic polyamine compounds, aliphatic polyamine compounds in which the amino group is protected by an organic group, aromatic polyamine compounds, etc. can be used.
[0135] Examples of aliphatic polyamine compounds include hexamethylenediamine. Examples of carbonates of aliphatic polyamine compounds include hexamethylenediamine carbamate. Examples of aliphatic polyamines in which the amino group is protected by an organic group include N,N'-dicinnamylidene-1,6-hexanediamine and compounds disclosed in Patent Document 11.
[0136] Examples of the aromatic polyamine compound include 4,4'-methylenedianiline, m-phenylenediamine, p-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-bis(4-aminophenoxy)biphenyl, m-phenylenediamine, p-phenylenediamine, 1,3,5-phenylenetriamine, 4,4'-(m-phenylenediisopropylidene)diphenylamine, 4,4'-(p-phenylenediisopropylidene)diphenylamine, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, and 4,4'-diaminobenzanilide.
[0137] The polyamine compounds listed above may be used alone or in combination of two or more. Hexamethylenediamine carbamate, 4,4′-diaminodiphenyl ether, and 2,2-bis[4-(4-aminophenoxy)phenyl]propane are preferably used.
[0138] The amount of the crosslinking agent added can be appropriately adjusted according to the desired crosslinking speed, mechanical strength, compression set resistance, thermal oxidative degradation resistance, and the like of the crosslinked product.
[0139] The polyamine crosslinking agent as component (C) is used in an amount of about 0.01 to 5 parts by weight, preferably about 0.05 to 3 parts by weight, relative to 100 parts by weight of the acrylic elastomer copolymer as component (A). If the amount of the polyamine crosslinking agent used is less than the above range, improvement in the compression set resistance cannot be expected. On the other hand, if the amount of the polyamine crosslinking agent used is more than the above range, the heat oxidative degradation resistance of the acrylic rubber may be deteriorated.
[0140] (D) As a crosslinking accelerator of a component, a guanidine compound, a diazabicycloolefin compound, or a crosslinking accelerator, such as an organic acid salt thereof, etc. are mentioned.
[0141] Examples of the guanidine compound include tetramethylguanidine, tetraethylguanidine, 1,3-diphenylguanidine, 1,3-di-o-tolylguanidine, etc. 1,3-diphenylguanidine, 1,3-di-o-tolylguanidine, or a combination thereof is preferred.
[0142] As the diazabicycloolefin compound, 1,8-diazabicyclo[5.4.0]-7-undecene is preferred.
[0143] As the organic acid salt of the diazabicycloolefin compound, an organic acid salt of 1,8-diazabicyclo[5.4.0]-7-undecene is preferred.
[0144] Examples of the organic acid used for the organic acid salt of 1,8-diazabicyclo[5.4.0]-7-undecene include monobasic organic acids and dibasic organic acids.
[0145] Examples of the monobasic organic acid include n-hexanoic acid, n-heptanoic acid, n-octanoic acid, 2-ethylhexanoic acid, n-decanoic acid, n-lauric acid, p-toluenesulfonic acid, and phenol. Examples of the dibasic organic acid include adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, terephthalic acid, phthalic acid, and phthalic acid. Preferred are monocarboxylic acids or dicarboxylic acids having 6 to 18 carbon atoms.
[0146] The crosslinking accelerator of component (D) is used in an amount of about 0.1 to 5 parts by weight, preferably about 0.3 to 3 parts by weight, relative to 100 parts by weight of the acrylic elastomer copolymer of component (A). If the amount of the crosslinking accelerator used is less than the above range, it will lead to a significant decrease in the crosslinking speed, a decrease in the mechanical properties of the acrylic rubber after crosslinking, and a decrease in the mechanical properties after heat aging. On the other hand, if the amount of the crosslinking accelerator used is more than the above range, it may cause a deterioration in the thermal oxidation degradation resistance of the acrylic rubber or a deterioration in the compression set resistance.
[0147] The cross-linkable acrylic rubber composition of the present invention may contain various additives such as fillers, processing aids, plasticizers, softeners, colorants, stabilizers, adhesion aids, mold release agents, conductivity-imparting agents, thermal conductivity-imparting agents, surface non-adhesives, tackifiers, flexibility-imparting agents, heat resistance-improving agents, flame retardants, ultraviolet absorbers, oil resistance-improving agents, scorch retardants, and lubricants as needed.
[0148] The filler includes: silica such as basic silica and acidic silica; metal oxides such as zinc oxide, calcium oxide, titanium oxide, and aluminum oxide; metal hydroxides such as magnesium hydroxide, aluminum hydroxide, and calcium hydroxide; carbonates such as magnesium carbonate, aluminum carbonate, calcium carbonate, and barium carbonate; silicates such as magnesium silicate, calcium silicate, sodium silicate, and aluminum silicate; sulfates such as aluminum sulfate, calcium sulfate, and barium sulfate; metal sulfides such as molybdenum disulfide, iron sulfide, and copper sulfide; synthetic hydrotalcite, diatomaceous earth, asbestos, lithopone (zinc sulfide / barium sulfide), graphite, carbon black (MT carbon black, SRF carbon black, FEF carbon black, etc.), carbon fluoride, calcium fluoride, coke, quartz fine powder, zinc white (zinc white), talc, mica powder, wollastonite, carbon fiber, aramid fiber, various whiskers, glass fiber, organic reinforcing agent, organic filler, etc.
[0149] As processing aids, there can be mentioned: higher fatty acids such as stearic acid, oleic acid, palmitic acid, and lauric acid; higher fatty acid salts such as sodium stearate and zinc stearate; higher fatty acid amides such as stearamide and oleamide; higher fatty acid esters such as ethyl oleate; higher aliphatic amines such as stearylamine and oleylamine; petroleum waxes such as carnauba wax and microcrystalline wax; polyethylene glycols such as ethylene glycol, glycerol, and diethylene glycol; aliphatic hydrocarbons such as vaseline and paraffin; silicone oils, silicone polymers, low molecular weight polyethylene, phthalates, phosphates, rosin, (halogenated) dialkylamines, (halogenated) dialkyl sulfones, surfactants, etc.
[0150] Examples of plasticizers include epoxy resins, phthalic acid derivatives, sebacic acid derivatives, etc. Examples of softeners include lubricating oils, process oils, coal tar, castor oil, calcium stearate, etc. Examples of antioxidants include phenylenediamines, phosphates, quinolines, cresols, phenols, dithiocarbamate metal salts, etc.
[0151] The above-mentioned compounding ingredients used as required can be mixed in the cross-linkable acrylic rubber composition of the present invention containing acrylic rubber, phenothiazine antioxidant, cross-linking agent and cross-linking accelerator, and mixed using a Banbury mixer, a pressure kneader, an open roll, etc. The cross-linkable mixture obtained is cross-linked by performing a primary cross-linking at about 120° C. to 250° C. for about 1 minute to 60 minutes and an oven cross-linking (secondary cross-linking) at about 120° C. to 200° C. for about 1 hour to 20 hours as required.
[0152] Example
[0153] Next, the present invention will be specifically described by way of examples. It should be noted that the present invention, including its effects, is not limited to the examples.
[0154] Reference Example 1
[0155] Preparation of compound (a)
[0156]
[0157] Compound (a) is produced by the following method.
[0158]
[0159] [Step 1][PTZ] → (a-1):
[0160] Into a 1000 ml four-necked flask equipped with a magnetic stirrer, a thermometer, a dropping funnel, a nitrogen inlet pipe and an outlet pipe, 60.0 g (301 mmol) of phenothiazine [PTZ] and 300 ml of N, N-dimethylformamide were added, and the temperature in the system was cooled to below 5°C under a nitrogen atmosphere. While keeping the temperature in the system below 10°C, 10.9 g (452 mmol) of sodium hydride was added and reacted for 1 hour. While keeping the temperature in the system below 20°C, 51.3 g (361 mmol) of iodomethane was added dropwise and the reaction was further carried out for 1 hour. After the reaction was completed, the reaction mixture was added to a saturated sodium chloride aqueous solution. The precipitated colorless solid was filtered out and dissolved in ethyl acetate. After washing it with a saturated sodium chloride aqueous solution, the organic layer was dried over anhydrous magnesium sulfate, and then the insoluble matter was filtered out. The volatile components were removed from the filtrate by reduced pressure distillation to obtain 67.8 g of a crude product (crude yield was 106%). By recrystallization using ethanol, 59.9 g of 10-methyl-10H-phenothiazine (a-1) was obtained as colorless needle crystals (yield: 93%).
[0161]
[0162] 1 H NMR (400MHz, Acetone-d6, δppm):
[0163] 3.39(s, 3H, NC H 3)
[0164] 6.91-6.98 (m, 4H, Ar)
[0165] 7.14 (dd, J=7.6Hz, J=1.6Hz, 2H, Ar)
[0166] 7.21(td, J=7.6Hz, J=1.6Hz, 2H, Ar)
[0167] [Step 2] (a-1) → (a-2):
[0168] Into a 500 ml four-necked flask equipped with a magnetic stirrer, a dropping funnel, a thermometer, a gas inlet and outlet, and a reflux condenser, 210 ml of N,N-dimethylformamide was added. Under a nitrogen atmosphere, while the internal temperature in the system was maintained below 10°C, 129.2 g (843 mmol) of phosphorus oxychloride was added dropwise, and the reaction was further carried out for 30 minutes. Next, 30 g (141 mmol) of N-methyl-10H-phenothiazine (a-1) obtained in the first step above was added, and the reaction was carried out at 60°C for 24 hours. After the reaction was completed, the contents were injected into an aqueous sodium acetate solution, and sodium bicarbonate was further added for neutralization. The product was extracted from the obtained aqueous solution using ethyl acetate, and the organic layer was washed once with a saturated sodium chloride aqueous solution. The organic layer was dried over anhydrous magnesium sulfate, and after filtering out the insoluble matter, the volatile components were removed from the filtrate under reduced pressure to obtain 33.8 g of a crude product as a red oily substance (crude yield was 99%). The crude product was subjected to column chromatography (carrier: Wakogel C300) using ethyl acetate as an eluent to remove low Rf components, thereby obtaining 33.6 g of the target crude product after removing low Rf components as a yellow solid (yield: 98%). Furthermore, recrystallization was performed using 70 ml of ethyl acetate to obtain 30.1 g of 10-methyl-10H-phenothiazine-3-carboxaldehyde (a-2) as yellow crystals (yield: 88%).
[0169]
[0170] 1 H NMR (400MHz, Acetoned6, δppm):
[0171] 3.49(s, 3H, NC H 3)
[0172] 7.00-7.06 (m, 2H, Ar)
[0173] 7.10 (d, J = 8.4 Hz, 1H, Ar)
[0174] 7.15-7.19 (m, 1H, Ar)
[0175] 7.22-7.28 (m, 1H, Ar)
[0176] 7.61 (d, J = 1.6 Hz, 1H, Ar)
[0177] 7.75(dd, J=8.4Hz, J=1.6Hz, 1H, Ar)
[0178] 9.85(s, 1H, -C H O)
[0179] [Step 3] (a-2) → (a):
[0180] Into a 500ml four-necked flask equipped with a magnetic stirrer, a thermometer, a gas inlet pipe and a gas outlet pipe, 220ml of tetrahydrofuran was added, and the internal temperature of the reaction container was cooled to below 10°C while replacing the reaction container with nitrogen. 8.4g (74.9mmol) of potassium tert-butoxide was added, followed by 26.9g (75.3mmol) of methyltriphenylphosphonium bromide, and the reaction was carried out for 30 minutes. 15.0g (62.2mmol) of compound (a-2) was added thereto, and the reaction was allowed to proceed at 10°C to 30°C for 2 hours. The obtained reaction mixture was added to a saturated sodium chloride aqueous solution, and the product was extracted with dichloromethane. After drying with anhydrous magnesium sulfate, the insoluble matter was filtered out, and the volatile components were removed from the filtrate by reduced pressure distillation to obtain 35.1g of residue. The residue was subjected to column chromatography (support: Wakogel C300) using dichloromethane as an eluent to remove triphenylphosphine oxide, and then recrystallized from ethanol to obtain 8.7 g of compound (a) as a light yellow solid (yield: 58%).
[0181] 1 H NMR (400MHz, CDCl3, δppm):
[0182] 3.37(s, 3H, NC H 3)
[0183] 5.14 (d, J = 10.8 Hz, 1H, C H 2=CH-Ph (trans relative to phenyl)
[0184] 5.61 (d, J = 17.6 Hz, 1H, C H 2=CH-Ph (cis relative to phenyl)
[0185] 6.59(dd, J=10.8Hz, 17.6Hz, 1H, CH2=C H -Ph)
[0186] 6.75 (d, J = 8.4 Hz, 1H, Ar)
[0187] 6.81 (d, J = 9.2 Hz, 1H, Ar)
[0188] 6.92(td, J=7.6Hz, 1.2Hz, 1H, Ar)
[0189] 7.11-7.23 (m, 4H, Ar)
[0190] Reference Example 2
[0191] Production of 10-pivaloyl-3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide [CD-SO2-PIV]
[0192]
[0193] Into a 1000 ml four-necked flask equipped with a magnetic stirrer, a thermometer, a nitrogen inlet and outlet, and a reflux condenser, 119.6 g (0.6 mol) of phenothiazine, 2.88 g of p-toluenesulfonic acid, and 480 ml of toluene were placed. After heating to 80°C, 141.9 g (1.2 mol) of α-methylstyrene was added, and the mixture was reacted for 1 hour under a nitrogen atmosphere.
[0194] After the reaction mixture was cooled to room temperature, toluene was distilled off under reduced pressure to obtain 265.5 g of a purple solid reaction product. By recrystallizing it with 1500 ml of ethanol, 179 g of crude 3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine [CD-S] was obtained as pale purple crystals (yield 68%). Furthermore, the crude CD-S was recrystallized again with ethanol to obtain 161 g of refined CD-S as colorless flaky crystals.
[0195] Into a 500 ml three-necked flask equipped with a magnetic stirrer, a thermometer and a reflux condenser, 68.7 g (158 mmol) of crude CD-S, 24.8 g (206 mmol) of pivaloyl chloride and 60 g of pyridine were added in sequence and reacted at 120°C for 1.5 hours. Pyridine was distilled off from the obtained reaction mixture under reduced pressure, and the residue was dissolved in 300 ml of dichloromethane. The organic layer was washed three times with 300 ml of saturated sodium chloride aqueous solution and dried over anhydrous magnesium sulfate. After filtering the magnesium sulfate, the volatile components were distilled off under reduced pressure from the filtrate to obtain 81.7 g of a red high-viscosity liquid.
[0196] The highly viscous liquid was dissolved in 250 ml of toluene and placed in a 1000 ml three-necked flask equipped with a magnetic stirrer, a thermometer and a reflux condenser. Then, 80 g of acetic acid and 107 g of 30% hydrogen peroxide solution were added in sequence and reacted at 100° C. for 2 hours.
[0197] After the contents were cooled to room temperature, the upper toluene layer was taken out and the volatile substances were distilled off under reduced pressure. 89 g of the obtained light red solid was recrystallized with a mixed solvent of ethanol / toluene (volume ratio 9:1) to obtain 70.3 g of CD-SO2-PIV as colorless needle crystals (the yield based on CD-S was 81%).
[0198] 1H NMR (300MHz, CDCl3, δppm):
[0199] 1.22(s, 9H, -C(C H 3)3)
[0200] 1.71(s, 12H, -C(C H 3)2-)
[0201] 7.19~7.30(m,12H)
[0202] 7.42 (d, J = 9.0 Hz, 2H)
[0203] 8.03 (d, J = 1.8 Hz, 2H)
[0204] Reference Example 3
[0205] Production of 3,7-bis(α,α-dimethylbenzyl)-10H-phenothiazine-5,5-dioxide [CD-SO2]
[0206]
[0207] Into a 500 ml four-necked flask equipped with a magnetic stirrer, a thermometer, a nitrogen inlet and outlet, and a reflux condenser, 24.9 g (0.125 mol) of phenothiazine, 0.6 g of p-toluenesulfonic acid, and 115 ml of toluene were placed, the temperature was raised to 80°C, 29.5 g (0.25 mol) of α-methylstyrene was added, and the mixture was reacted for 1 hour under a nitrogen atmosphere.
[0208] Next, 30 g of acetic acid was added to the reaction mixture, and then 42.5 g of 30% hydrogen peroxide solution was added in 5 portions, and the mixture was further reacted at 80° C. for 2 hours. The contents were cooled to room temperature, and after standing, the upper toluene layer was injected into 500 ml of methanol. After standing at room temperature overnight, 42.5 g of crude CD-SO2 was obtained as pale yellow crystals (yield 72%). It was recrystallized from ethanol to obtain 38 g of CD-SO2 as pale yellow needle crystals (yield 65%).
[0209] Reference Example 4
[0210] [Production of Acrylic Elastomer Copolymer A]
[0211] Place the following substances in a separable flask equipped with a thermometer, stirrer, nitrogen inlet tube and condenser coil:
[0212]
[0213] After nitrogen substitution to fully remove oxygen from the system, add the following:
[0214] Sodium formaldehyde sulfoxylate (Rongalit, Fujifilm Wako Pure Chemical Industries, Ltd.) 0.008 parts by weight
[0215] Tert-butyl hydroperoxide (Perbutyl H69, a product of NOF) 0.0047 parts by weight
[0216] The polymerization reaction was initiated at room temperature and continued until the polymerization conversion rate reached 90% or more. The obtained aqueous latex was coagulated with a 10 wt% sodium sulfate aqueous solution, washed with water, and dried to obtain an acrylic rubber A. The Mooney viscosity PML of the obtained acrylic rubber elastic copolymer A was 1+4 (100℃) is 31.
[0217] Its molar fraction composition is given by the following formula 1 H-NMR (400 MHz, acetone d6, δ ppm) showed that the content of compound (a) was 0.41 mol % and the content of EA+MBF was 99.59 mol %.
[0218] α: The integral value of the signal between 6.5 and 7.5 ppm
[0219] β: The integral value of the signal between 3.2 and 5.0 ppm
[0220] Compound (a) (mol%) = 200 × α / (2α + 7β)
[0221] EA+MBF (mol%)=100-compound (a)
[0222] The approximate weight fraction composition was calculated from the following formula. As a result, the compound (a) was 1.0 weight % and EA+MBF was 99.0 weight %.
[0223] Compound (a) (weight %) = (compound (a) (mol %) × 239.34 × 100)
[0224] / [Compound (a) (mol%) × 239.34 + (EA + MBF (mol%)) × 100.8)]
[0225] EA+MBF (weight %)=100-compound (a) (weight %)
[0226] Reference Comparative Example 1
[0227] The copolymerization reaction was carried out in the same manner as in Reference Example 4 except that the following monomer mixture was used to prepare an acrylic rubber B. The Mooney viscosity PML of the obtained acrylic elastomer copolymer B was 1+4 (100℃) is 32.
[0228] Loading monomer mixture
[0229] Ethyl acrylate [EA] 98.4 parts by weight
[0230] Mono-n-butyl fumarate [MBF] 1.6 parts by weight
[0231] Reference Example 5
[0232] [Production of Acrylic Elastomer Copolymer C]
[0233] The copolymerization reaction was carried out in the same manner as in Reference Example 4 except that the following monomer mixture was used to prepare an acrylic rubber C. The Mooney viscosity PML of the obtained acrylic elastomer copolymer C was 1+4 (100℃) is 30.
[0234] Ethyl acrylate [EA] 97.9 parts by weight
[0235] Mono-n-butyl fumarate [MBF] 1.6 parts by weight
[0236] Compound (a) of Reference Example 1 0.5 parts by weight
[0237] The molar fraction composition was determined from the formula of Reference Example 4. As a result, the compound (a) accounted for 0.20 mol % and EA+MBF accounted for 99.80 mol %.
[0238] The approximate weight fraction composition was determined from the formula of Reference Example 4, and the composition of the compound (a) was 0.5% by weight and that of EA+MBF was 99.5% by weight.
[0239] Reference Example 6
[0240] [Production of Acrylic Elastomer Copolymer D]
[0241] The copolymerization reaction was carried out in the same manner as in Reference Example 4 except that the following monomer mixture was used to obtain an acrylic rubber D. The Mooney viscosity PML of the obtained acrylic elastomer copolymer D was 1+4 (100℃) is 26.
[0242]
[0243] The molar fraction composition was determined from the formula of Reference Example 4. As a result, the compound (a) accounted for 0.31 mol % and EA+BA+MBF accounted for 99.69 mol %.
[0244] The approximate weight fraction composition was determined from the following formula. As a result, the compound (a) accounted for 0.7 weight % and EA+BA+MBF accounted for 99.3 weight %.
[0245] Compound (a) (weight %) = (compound (a) (mol %) × 239.34 × 100)
[0246] / [Compound (a) (mol%) × 239.34 + (EA + BA + MBF (mol%)) × 110.6)]
[0247] EA+BA+MBF (weight %)=100-compound (a) (weight %)
[0248] Reference Comparative Example 2
[0249] The copolymerization reaction was carried out in the same manner as in Reference Example 4 except that the following monomer mixture was used to prepare the acrylic rubber E. The Mooney viscosity PML of the obtained acrylic elastomer copolymer E was 1+4 (100℃) is 26.
[0250] Loading monomer mixture
[0251] Ethyl acrylate [EA] 58.4 parts by weight
[0252] n-Butyl acrylate [BA] 40.0 parts by weight
[0253] Mono-n-butyl fumarate [MBF] 1.6 parts by weight
[0254] Reference Example 7
[0255] [Production of Acrylic Elastomer Copolymer F]
[0256] The copolymerization reaction was carried out in the same manner as in Reference Example 4 except that the following monomer mixture was used to prepare an acrylic rubber F. The Mooney viscosity PML of the obtained acrylic elastomer copolymer F was 1+4 (100℃) is 24.
[0257]
[0258] The molar fraction composition was determined from the formula of Reference Example 4. As a result, the compound (a) accounted for 0.24 mol % and EA+BA+MBF accounted for 99.76 mol %.
[0259] The approximate weight fraction composition was determined from the formula of Reference Example 6, and the compound (a) accounted for 0.5 weight % and EA+BA+MBF accounted for 99.5 weight %.
[0260] Example 1
[0261]
[0262]
[0263] Among the above components, acrylic elastomer copolymer A, SRF carbon black, stearic acid and polyoxyethylene stearyl ether phosphate were mixed using a Banbury mixer, and the resulting mixture was mixed with the remaining components using an open roll to obtain a crosslinkable acrylic rubber composition.
[0264] The composition was cross-linked once at 180°C for 8 minutes using a 100-ton press molding machine, and further cross-linked in an oven at 175°C for 4 hours to obtain a sheet-like cross-linked product with a thickness of about 2 mm and a cylindrical cross-linked product with a diameter of about 29 mm and a height of about 12.5 mm.
[0265] The crosslinking characteristics of the acrylic rubber composition and the physical properties of its crosslinked product were measured as follows.
[0266] Mooney scorch test: According to JIS K6300-1 (125°C) corresponding to ISO 289-1, using a Mooney viscometer AM-3 manufactured by Toyo Seiki Seisaku-sho, the values of minimum Mooney viscosity (ML min) and scorch time (t5) were measured;
[0267] Cross-linking test: In accordance with JIS K6300-2 corresponding to ISO 6502 (180°C, 12 minutes), the values of ML, MH, tc(10) and tc(90) were measured using a rotorless rheometer RLR-3 manufactured by Toyo Seiki Seisaku-sho., Ltd.
[0268] ML: Minimum torque
[0269] MH: Maximum torque
[0270] tc(10): time required for the cross-linking torque to reach ML+(MH-ML)×0.1
[0271] tc(90): The time required for the cross-linking torque to reach ML+(MH-ML)×0.9
[0272] Normal physical properties: Measured on post cured sheets in accordance with JIS K6251 corresponding to ISO 37 and JIS K6253 corresponding to ISO 37.
[0273] Air heating aging test: According to JIS K6257 corresponding to ISO 188, the post-cured sheet was measured; (190°C: 100 hours, 200 hours, 300 hours, 400 hours, 500 hours, 600 hours) Oil immersion test: According to JIS K6258 corresponding to ISO 1817, after immersion in oil (IRM903 oil) at 150°C for 168 hours, the change rate of each normal physical property and the volume swelling rate compared with before oil immersion were calculated;
[0274] Air heating aging test-oil immersion-air heating aging composite test:
[0275] According to JIS K6257 corresponding to ISO 188, an air heating aging test was performed at 175°C for 150 hours, according to JIS K6258 corresponding to ISO 1817, an oil (IRM903 oil) immersion test was performed at 150°C for 168 hours, and according to JIS K6257 corresponding to ISO 188, an air heating aging test was performed at 190°C for 300 hours, and the change rate of each normal physical property was calculated;
[0276] Compression set test: in accordance with JIS K6262 corresponding to ISO 815-1 (175°C: 70 hours, 500 hours) Comparative Example 1
[0277] In Example 1, CD-SO2-PIV was not used.
[0278] Comparative Example 2
[0279] In Example 1, acrylic elastomer copolymer B was used instead of acrylic elastomer copolymer A.
[0280] Comparative Example 3
[0281] In Comparative Example 2, 1 part by weight of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine (Nocrac CD, a product of Ouchi Shinko Chemical Industry Co., Ltd.) was used instead of CD-SO2-PIV.
[0282] Example 2
[0283] In Example 1, the following components were used as the cross-linkable acrylic rubber composition.
[0284]
[0285] Comparative Example 4
[0286] In Example 2, CD-SO2 was not used.
[0287] Comparative Example 5
[0288] In Example 2, acrylic elastomer copolymer B was used instead of acrylic elastomer copolymer C.
[0289] Comparative Example 6
[0290] In Comparative Example 5, 1 part by weight of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine (Nocrac CD) was used instead of CD-SO 2 .
[0291] Example 3
[0292] In Example 1, the following components were used as the cross-linkable acrylic rubber composition.
[0293]
[0294] Comparative Example 7
[0295] In Example 3, CD-SO2 was not used.
[0296] Comparative Example 8
[0297] In Example 3, acrylic elastomeric copolymer E was used instead of acrylic elastomeric copolymer D.
[0298] Comparative Example 9
[0299] In Comparative Example 8, 1 part by weight of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine (Nocrac CD) was used instead of CD-SO 2 .
[0300] Example 4
[0301] In Example 1, the following components were used as a cross-linkable acrylic rubber composition, and the cross-linked product of the acrylic rubber composition was subjected to a toluene immersion-air heating aging composite test.
[0302]
[0303]
[0304] Toluene immersion-air heating aging composite test:
[0305] After a toluene immersion test was performed at room temperature for 168 hours in accordance with JIS K6258 corresponding to ISO 1817, toluene was removed from the test piece by air drying, and then an air heating aging test was performed at 190° C. for 300 hours in accordance with JIS K6257 corresponding to ISO 188.
[0306] Comparative Example 10
[0307] In Example 4, CD-SO2 was not used.
[0308] Comparative Example 11
[0309] In Example 4, acrylic elastomer copolymer E was used instead of acrylic elastomer copolymer F.
[0310] Comparative Example 12
[0311] In Comparative Example 11, 1 part by weight of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine (Nocrac CD) was used instead of CD—SO 2 .
[0312] The results obtained in the above Examples 1 to 4 and Comparative Examples 1 to 12 are shown in the following Tables 1 to 4 and Figure 1 to Figure 15 middle.
[0313] [Table 1]
[0314]
[0315]
[0316] [Table 2]
[0317]
[0318]
[0319] [Table 3]
[0320]
[0321]
[0322] [Table 4]
[0323]
[0324]
[0325] For Example 1 and Comparative Examples 1 to 3, ΔΔEb, which indicates the degree of extraction of the antioxidant from the crosslinked product by the oil immersion test, was calculated by the following formula. The results were -12 for Example 1, -10 for Comparative Example 1, -25 for Comparative Example 2, and -95 for Comparative Example 3.
[0326] ΔΔEb = ΔEb (change rate of elongation at break in air heating aging test-oil immersion test-air heating aging composite test) - ΔEb (change rate of elongation at break in 190°C, 300 hours air heating aging test)
[0327] In addition, for Example 4 and Comparative Examples 10 to 12, ΔΔEb indicating the degree of extraction of the antioxidant from the crosslinked product by the toluene immersion test was calculated by the following formula. The results were -7 for Example 4, -7 for Comparative Example 10, -28 for Comparative Example 11, and -38 for Comparative Example 12.
[0328] ΔΔEb = ΔEb (change rate of elongation at break in toluene immersion test-air heating aging composite test) - ΔEb (change rate of elongation at break in 190°C, 300 hours air heating aging test)
[0329] The following conclusions can be drawn from the above results.
[0330] (1) In the air heating aging test, it is found that the reduction in breaking strength of Example 1 is suppressed compared with Comparative Examples 2 and 3. This is considered to be due to the cross-linking effect of the anti-aging component chemically bonded to the acrylic elastomer. The same tendency is also shown in Comparative Examples 5 and 6 and Example 2, Comparative Examples 8 and 9 and Example 3, and Comparative Examples 11 and 12 and Example 4.
[0331] (2) In Examples 1 to 3 (after the elongation at break slightly decreased at the initial stage of the test), the rubber elasticity remained almost constant for a long period of time, whereas in Comparative Examples 1, 4, and 7, the elongation at break decreased from the middle stage of the test, indicating that the rubber elasticity was lost. On the other hand, in Comparative Examples 2, 3, 5, 6, 8, 9, 11, and 12, a significant increase in the elongation at break and a significant decrease in the breaking strength due to softening degradation were observed from the initial stage of the test, indicating that the mechanical strength of the cross-linked product decreased.
[0332] (3) In the oil immersion test-air heating aging composite test, it can be seen that the elongation at break of Comparative Example 3 is significantly reduced compared with the elongation at break of Example 1 and Comparative Example 1. It is speculated that the reason is that the anti-aging agent is extracted from the cross-linked product by the oil immersion test. On the contrary, in Comparative Example 2, an increase in elongation at break is observed. It can be considered that the reason is that the phenothiazine anti-aging agent is difficult to be extracted by oil and remains in the rubber. The absolute value of the value of ΔΔEb, which represents the degree of extraction of the anti-aging agent from the cross-linked product by the oil immersion test, is small, which also indicates this situation. On the other hand, in Example 1 and Comparative Example 1, since the anti-aging component is chemically bonded to the acrylic elastomer copolymer, it is speculated that it is exempted from being extracted by oil, and as a result, the reduction of elongation at break can be suppressed.
[0333] (4) It is believed that the greater the absolute value of the ΔΔEb value indicating the degree of extraction of the antioxidant from the cross-linked product by the toluene immersion test, the more antioxidant is extracted and the lower the residual rate in the cross-linked product. Therefore, these results show that the antioxidant component produced by the copolymeric aging agent (a) is not easily extracted by toluene and most of it remains in the cross-linked product (Example 4, Comparative Example 10). In addition, by comparing Example 4 and Comparative Example 12, it can be seen that the reduction in the elongation at break of Example 4 is relatively small, which can be said to be the effect of using the copolymeric aging agent (a) and the phenothiazine antioxidant CD-SO2 in combination.
[0334] (5) The reduction in breaking strength of Example 1 and Comparative Example 1 was smaller than that of Comparative Examples 2 and 3. This is believed to be mainly due to the cross-linking effect of the anti-aging component chemically bonded to the acrylic elastomer. In Comparative Example 2, the reduction in breaking strength due to softening deterioration was significant. This is a phenomenon unique to rubbers compounded with phenothiazine-based anti-aging agents.
[0335] (6) The rubber member obtained by crosslinking the composition of the present invention can maintain its mechanical strength and rubber elasticity for a long period of time under severe thermal oxidative degradation conditions or severe extraction and chemical degradation conditions using a liquid medium such as oil.
Claims
1. A cross-linkable acrylic rubber composition, characterized in that: The cross-linkable acrylic rubber composition contains the following ingredients: (A) an acrylic elastomer copolymer composed of a copolymerizable antioxidant represented by the general formula [I], an alkyl (meth)acrylate monomer and / or an alkoxyalkyl (meth)acrylate monomer, and an α,β-unsaturated carboxylic acid monomer; In the general formula [I], R 1 is a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, R 2 is a hydrogen atom or a methyl group, and A is a direct bond, an oxygen atom or a sulfur atom; (B) a phenothiazine antioxidant represented by the general formula [II]; In the general formula [II], R 3 is a hydrogen atom, a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, or an acyl group represented by the following general formula [III], R 4 is an aralkyl group having 7 to 20 carbon atoms; In the general formula [III], R 5 It is a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms; (C) a polyamine cross-linking agent; and (D) Cross-linking accelerator.
2. The cross-linkable acrylic rubber composition according to claim 1, wherein In the copolymerizable antioxidant represented by the general formula [I], A is a sulfur atom.
3. The cross-linkable acrylic rubber composition according to claim 1, wherein The component (A) is an acrylic elastomer copolymer composed of a copolymerizable antioxidant represented by the general formula [I], an alkyl acrylate monomer, and an α,β-unsaturated carboxylic acid monomer.
4. The cross-linkable acrylic rubber composition according to claim 3, wherein Ethyl acrylate and / or n-butyl acrylate are used as the alkyl acrylate monomer.
5. The cross-linkable acrylic rubber composition according to claim 1, wherein The component (C) polyamine crosslinking agent is hexamethylenediamine carbamate, 4,4'-diaminodiphenyl ether or 2,2-bis[4-(4-aminophenoxy)phenyl]propane.
6. The cross-linkable acrylic rubber composition according to claim 1, wherein The crosslinking accelerator of the component (D) is 1,8-diazabicyclo[5.4.0]-7-undecene or an organic acid salt thereof.
